Understanding patient preferences for private healthcare services among the general Hungarian adult population using discrete choice experiment - Balázs Kertesz; Klára Bíró; Péter Balogh (Discover Social Science and Health, 2026)
Abstract As private healthcare plays an increasingly prominent role in Hungary’s dual healthcare system, understanding patient preferences has become essential for health policymakers and healthcare providers. Background data indicate significant underfunding in Hungary’s public healthcare system, leading to long waiting times and limited access—key drivers of private-sector growth. This study investigates attributes associated with stated choice in private healthcare settings using a discrete choice experiment with a quota-representative Hungarian adult survey sample ( n = 1,014). A best-worst scaling (BWS) analysis preceded the DCE to identify relevant attributes. The final DCE experimental design included cost, provider distance, appointment availability, provider reputation, and clinic type. The respondents were asked to choose in 8 decision situations, each of which included three private health service options and a no-choice option (to stay in public healthcare). The model estimation was performed using a conditional logit (CL) specification, and willingness-to-pay (WTP) calculations were also conducted. Results revealed that provider distance was the most important attribute (40.01%), followed by cost (32.31%) and appointment availability (19.13%). Institutional reputation and provider type were less influential. The study concludes that Hungarian patients approach private healthcare pragmatically, prioritizing accessibility and affordability. These results may inform policy and service-planning discussions on access, affordability, and regional inequalities in Hungary’s mixed public–private healthcare system.